Kesenjangan (GAP) Pelayanan Dan Kepuasan Konsumen Studi Kasus Minimarket X di Jakarta Timur - Irma Sari Permata; Asriyal Asriyal (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2013)
The man priorities that need to be considered by the marketers is to provide the best possible services to consumers. Good service for customer satisfaction. Above a level of customer satisfaction can be measured by comparing services between customer expectations of service quality they want with the fact that acceptance or perceived.